2019
DOI: 10.1111/jocn.14749
|View full text |Cite
|
Sign up to set email alerts
|

Operative and anaesthetic factors influencing on delirium in the intensive care unit: An Analysis of electronic health records

Abstract: The occurrence rate of postoperative delirium, which affects the patient outcomes negatively, is expected to increase as the number of operations associated with delirium increases yearly in Korea.However, a cognitive disorder following anaesthesia often hinders the early detection of symptom of delirium. Therefore, the identification of the risk factors that influence the postoperative delirium is important to provide early preventive intervention for the patients with those risk factors. | BACKG ROU N DThe r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Phrased differently, aseptic inflammation due to hip fracture or the consequent surgery may aggravate the existing neurocognitive deficits in neurodegenerative and neuro-inflammatory disease, thereby triggering delirium symptoms and the onset of full-blown delirium. In contrast, other known predisposing factors of delirium such as the operative time [49], preadmission deliriogenic drugs and polypharmacy [50, 51], and postoperative pain [52, 53] were not correlated with the diagnosis of delirium or the severity of delirium symptoms. Nevertheless, the current study showed that increased blood loss during surgery may further increase the severity of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Phrased differently, aseptic inflammation due to hip fracture or the consequent surgery may aggravate the existing neurocognitive deficits in neurodegenerative and neuro-inflammatory disease, thereby triggering delirium symptoms and the onset of full-blown delirium. In contrast, other known predisposing factors of delirium such as the operative time [49], preadmission deliriogenic drugs and polypharmacy [50, 51], and postoperative pain [52, 53] were not correlated with the diagnosis of delirium or the severity of delirium symptoms. Nevertheless, the current study showed that increased blood loss during surgery may further increase the severity of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Phrased differently, aseptic inflammation due to hip fracture or the consequent surgery may aggravate the existing neurocognitive deficits in neurodegenerative and neuro-inflammatory disease thereby triggering delirium symptoms and the onset of full-blown delirium. In contrast, other known predisposing factors of delirium such as the operative time (59) , pre-admission deliriogenic drugs and polypharmacy (60,61) , and postoperative pain (62, 63) were not correlated with the diagnosis of delirium. On the other hand, the current study showed that increased blood loss during surgery may further increase the severity of delirium.…”
Section: Discussionmentioning
confidence: 77%
“…CAM-ICU was developed as a short, accurate and reliable instrument for doctors and nurses to identify delirium in ICU patients. [6][7][8]…”
Section: Environment As a Treatment Toolmentioning
confidence: 99%